Electroanalysis at activated electrodes - Moorcroft, M; Moorcroft, Matthew James (2002)
﻿ This thesis details advances made within the field of electroanalytical chemistry through the use of working electrodes that have been activated through application of ultrasound, heat, geometry, chemical modification or composition. Initially the thesis reports the enhanced analytical utility of chemically and compositionally modified working electrodes when directed towards the detection and determination of NO3¯ and NO2¯ anions in environmental samples. This has been achieved through the use of electrodes that have been a) modified with a Cu deposit and b) fashioned from a Cu-Ni alloy. Nitrate and nitrite anions have been successfully determined in a variety of passivating matrices, at analytically relevant detection limits of the order of 10-6 M with a dynamic linear range extending from 10 to 200 μM. The methods presented have been shown to surpass existing electrochemical techniques in terms of nitrate/nitrite speciation through separation of the voltammetric signals, where existing analyses have reported the intereference of both species when present in the same solution. The use of ultrasound as a further enhancement to the sensitivity and versatility of the electrochemical detection of nitrate at a chemically modified electrode is then presented. The influence of ultrasound is shown to remove a portion of the deposited copper, but a significant catalytic layer remains, resulting in greater sensitivity during insonation. The effect of temperature on electrochemical systems involving one- and two-electron redox reactions of K4Fe(CN)6, Ru(NH3)6Cl3, Fe(C5H5)2, N,N,N',N'tetramethylphenylenediamine, N,N'dimethylphenylenediamine and tris(4- bromophenyl)amine have been studied under hydrothermal conditions using a novel hydrodynamic method based on a conventional channel flow cell where the working electrode is heated by radio frequency radiation. The diffusion activation parameters obtained with the radio frequency channel cell and computer simulation were compared with independent data from microelectrode high temperature experiments. The application of the heated flow cell as a tool for mechanistic studies is discussed with the investigation of the well characterised ECE reaction of m-iodo-nitrobenzene in acetonitrile, giving a value of 80 ± 5 kJ mol-1 for the activation energy of the rate constant for the decomposition of the m-iodo-nitrobenzene radical anion. This represents the first observation of an ECE or mechanistically complex reaction at a locally heated electrode. The work presented in the final two chapters of this thesis examines the enhanced activation achieved from modification of the electrode geometry, and in particular the application of microelectrodes to the development of electroanalytical techniques. The electrochemical reduction of the inhalation anaesthetic agent enflurane (2-chloro-1,1,2- trifluoroethyl difluoromethyl ether) is reported at a variety of microelectrode substrates (Au, Ag, Cu, Pt and glassy carbon) with electrode dimensions varying from 5 to 60 μm. The solvents water, dimethylsulfoxide and acetonitrile were investigated along with the supporting electrolytes potassium chloride, tetrabutylammonium hexafluorophosphate and various tetraalkylammonium perchlorates. The use of a gold microelectrode with dimethyl sulfoxide solvent and tetraethylammonium perchlorate as the supporting electrolyte was found to give well-defined voltammetry. Linear calibration curves were obtained between 0 and 2 % v/v (gaseous additions) or up to 135 mM (gravimetric additions), offering scope for the development of a rapid, inexpensive electrochemical gas sensor. The analytical utility of the system has been investigated in the presence of oxygen and nitrous oxide in DMSO solvent. The superoxide anion radical, formed from the electro-reduction of dissolved oxygen, is shown to react with enflurane complicating their simultaneous detection. The kinetics of the enflurane / superoxide reaction are found to be first order with respect to both superoxide and enflurane with a rate constant of 0.25 M-1 s-1 determined by three independent methods: steady-state voltammetry, digital simulation of cyclic voltammetric data and UV/Vis spectroscopic analysis.